Racial/ethnic differences in health insurance adequacy and consistency among children: Evidence from the 2011/12 National Survey of Children’s Health - Tulay G. Soylu; Eman Elashkar; Fatemah Aloudah; Munir Ahmed; Panagiota Kitsantas (Journal of Public Health Research, 2018)
Background: Surveillance of disparities in healthcare insurance, services and quality of care among children are critical for properly serving the medical/healthcare needs of underserved populations. The purpose of this study was to assess racial/ethnic differences in children’s (0 to 17 years old) health insurance adequacy and consistency (child has insurance coverage for the last 12 months). Design and methods: We used data from the 2011/2012 National Survey of Children’s Health (n=79,474). Descriptive statistics and logistic regression analyses were conducted to examine the distribution and influence of several sociodemographic/family related factors on insurance adequacy and consistency across different racial/ethnic groups. Results: Stratified analyses by race/ethnicity revealed that white and black children living in households at or below 299% of the Federal Poverty Level (FPL) were approximately 29 to 42% less likely to have adequate insurance compared to children living in families of higher income levels. Regardless of race/ethnicity, we found that children with public health insurance were more likely to have adequate insurance than their privately insured counterparts, while adolescents were at greater risk of inadequate coverage. Hispanic and black children were more likely to lack consistent insurance coverage. Conclusions: This study provides evidence that racial/ethnic differences in adequate and consistent health insurance exists with both white and minority children being affected adversely by poverty. Establishing outreach programs for low income families, and cross-cultural education for healthcare providers may help increase health insurance adequacy and consistency within certain underserved populations.